Women's Leadership Management in Developing the Character of Al Munawwir Students Based on Religious Values - Huda, Syariful Huda; Nai'imah; Muhammad Azmi Auf; Abdillah Naufal Abror; Rafi Pradipa (Kopertais Wilayah III Yogyakarta, 2025)
This study was conducted to analyze women's leadership management in the character development of students (santri) at Al-Munawir Islamic Boarding School (Pondok Pesantren Al-Munawir) in Krapyak, Yogyakarta, particularly those based on religious values. This research is a qualitative study using a case study approach. Primary data were obtained through in-depth interviews with the boarding school caretaker, Mrs. Nyai Idah, who leads the Fatimiyah and L dormitory, as well as through direct observation within the pesantren environment. Meanwhile, secondary data were collected from literature reviews related to women's leadership, character education, and religious values in Islamic boarding schools. The results show that the women's leadership applied here has strong characteristics in shaping the students' personalities through exemplary behavior, discipline, and both spiritual and emotional approaches. Furthermore, the findings indicate that religious values serve as the main foundation in the character-building process, such as sincerity, responsibility, manners, and independence, which are consistently instilled in the students' daily lives. The implications of this research suggest that women's leadership in Islamic boarding schools can make a significant contribution to the character formation of students, especially when managed with strong Islamic values. This also opens up opportunities to strengthen the role of women in faith-based educational institutions